2015
DOI: 10.1016/j.intfin.2014.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Herding dynamics in exchange groups: Evidence from Euronext

Abstract:  We examine whether joining an exchange group confers an effect over herding in the group's member-markets and if this effect persists when accounting for various domestic and international market states, the dynamics of the group's member-markets and the outbreak of financial crises  We test for the above in the context of the Euronext, which contains four equity markets (Belgium, France, the Netherlands and Portugal)  Herding is significant post-merger in all four markets; herding in Portugal is significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 70 publications
2
48
1
Order By: Relevance
“…It is also possible that intraday strategies generate correlated trades themselves, due to them either being programmed to focus on similar signals (those based on computer algorithms; see Sornette and von der Becke, 2011;Chaboud et al, 2014) or based on similar technical trading rules (the case of day trading). Also, as mentioned previously, earlier event studies (Andrikopoulos et al, 2014;Economou et al, 2015) 15 have demonstrated that joining 15 Andrikopoulos et al, (2014) and Economou et al, (2015) compare herding in Euronext's four constituent equity markets prior to and after their merger into the group. Andrikopoulos et al, (2014) measure herding at the monthly frequency for the January 1993 -October 2009 period and show that herding in Belgium, France and the Netherlands is significant (insignificant) following (before) these markets' merger into the Euronext; no evidence of herding significance was detected for Portugal, be it before or after its entry into the group.…”
Section: Introductionmentioning
confidence: 59%
See 3 more Smart Citations
“…It is also possible that intraday strategies generate correlated trades themselves, due to them either being programmed to focus on similar signals (those based on computer algorithms; see Sornette and von der Becke, 2011;Chaboud et al, 2014) or based on similar technical trading rules (the case of day trading). Also, as mentioned previously, earlier event studies (Andrikopoulos et al, 2014;Economou et al, 2015) 15 have demonstrated that joining 15 Andrikopoulos et al, (2014) and Economou et al, (2015) compare herding in Euronext's four constituent equity markets prior to and after their merger into the group. Andrikopoulos et al, (2014) measure herding at the monthly frequency for the January 1993 -October 2009 period and show that herding in Belgium, France and the Netherlands is significant (insignificant) following (before) these markets' merger into the Euronext; no evidence of herding significance was detected for Portugal, be it before or after its entry into the group.…”
Section: Introductionmentioning
confidence: 59%
“…Andrikopoulos et al, (2014) measure herding at the monthly frequency for the January 1993 -October 2009 period and show that herding in Belgium, France and the Netherlands is significant (insignificant) following (before) these markets' merger into the Euronext; no evidence of herding significance was detected for Portugal, be it before or after its entry into the group. Economou et al, (2015) measure herding at the daily frequency for the January 1990 -December 2012 period and show that herding in Belgium, France and the Netherlands is significant (insignificant) following (before) these markets' merger into the Euronext; evidence of herding significance was detected for Portugal both before and after its entry into the group. Aside from examining herding at intraday frequencies (compared to the monthly and daily ones of these studies) our work differs from the above studies, since, instead of investigating the effect of Euronext-membership over herding in each of these four markets individually, it investigates a cross-border exchange group (more specifically, the Euronext) has led herding to grow in significance in the group's member markets.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…This work is interesting because it compares different models. They not only presented the two methodologies based on individual returns of assets, CSSD and CSAD, but also the methodology of Hwang and Salmon (2004) The study of crises periods is important because there is no agreement on the effect of crises on herding behavior (Economou et al, 2015). For instance, according to Kim and Wei (2002), in the Asian crisis of 1997, foreign investors were feedback traders (buying when the market rises and selling when the market falls), systematically ignoring the fundamentals.…”
Section: Main Methodologies and Empirical Studiesmentioning
confidence: 99%